The Effectiveness of Using E-Learning on Social Studies Learning Outcomes in Class VIII of PGRI Mekarmukti Middle School Garut - Akhmad Deni, Akhmad Deni; Triani Widyanti; Slamet Nopharipaldi Rohman (SAHUR Journal, 2024)
Education as something that is familiar in people's lives, especially in the current situation, the education system in Indonesia has experienced development, moreover because of the relatively rapid movement in the field of education. The teaching and learning process is basically carried out manually, that is, face-to-face meetings between educators and students are carried out at schools, using the Teacher Centered Learning (TCL) approach. The research method used is quantitative method with this type of research is Quasi Experimental Design (quasi-experimental). Data collection techniques were carried out by observation, interviews and documentation studies. Data analysis techniques used the normality test, homogeneity test, hypothesis testing and normalized gain test to identify improvements in the results of the research conducted. The results of data analysis and statistical calculations using a Likert scale show that the attitude of students towards learning media based on E-Learning in general shows a very good attitude and the attitude of students towards learning media based on E-Learning for each individual shows a very good attitude, so it can be concluded that the interpretation of the scale of attitudes of students towards learning media based on E-Learning is in the very good category.